Impact of mammography screening on the treatment of women diagnosed with breast cancer - Ugioni, Laura; Carminatti, Laura; Rovaris, Alessandra Beatris; Ramos, Luiza (Mastology, 2020)
Objective: To evaluate the influence of mammographic screening on the treatment of women with previous diagnosis of breast cancer. Method: Cross-sectional, descriptive, observational study, with primary and secondary data collection and quantitative approach. It was performed in a high complexity hospital in the South region of Santa Catarina, Brazil, where patients with previous history of breast cancer were evaluated during the period from 2012 to 2017, and who were undergoing oncological follow-up at the same hospital. The variables were expressed as frequency and percentage. Inferential statistical analyses were performed with a significance level of alpha = 0.05 and, therefore, 95% confidence interval. Therefore, the confidence interval was 95%. Associations between variables were investigated using the Pearson’s χ² and the likelihood ratio tests. Results: Among the 99 analyzed patients, 58.6% annually performed the examination and 49.5% had elapsed less than 12 months between the last performed mammogram and the diagnosis. There was a higher frequency of stage I disease, corroborating the results that 74.7% of patients underwent breastconserving surgeries and 68.7% underwent sentinel lymph node biopsy, rather than extensive surgeries. Regarding the treatment of choice, patients with annual or biennial mammographic frequency had similar surgical and chemotherapeutic outcomes in relation to patients who had a mammogram without defined frequency or who had never undergone it. Conclusion: Patients who underwent mammography on an annual frequency and those whose time between the last mammogram and the diagnosis of cancer was less than 12 months had tumors of lesser extent at diagnosis; however, it did not influence the type of treatment chosen.